Beneficiation of fine ores using the Longi wet high magnetic separator - Makhula, Mpho Johanna (My University, 2014)
Magnetic separation has been used since 1955 for processing a variety of minerals from iron ore in steel production to the desulphurisation of coal. The accumulation of such fines and slimes during mining operations and the increasing global demand for quality products motivated the use of the semi-continuous pilot wet high intensity magnetic separator (WHIMS) introduced in 2008. Its unique features were considered to be favourable for beneficiating a Sishen low grade hematite-rich ore and an ash-rich Witbank coal. An automated Mineral Liberation Analyser (MLA) was used to characterise the size distribution of the hematite-rich material thereby providing an estimated grade at the same time. This type of analysis characterises mineral types in terms of particle size and elemental composition, specific density, weight percent, area of particle, particle shape, circularity and equivalent circle diameter. However, for this research study only size and elemental composition were considered. The application of the Longi LGS 500 WHIMS for beneficiating a low grade South African iron ore material was investigated by determining the effects of changing the operating parameters of pulp solids, magnetic field intensity and the pulsation frequency. This was followed by a 33 full factorial design which consisted of twenty seven (27) test matrix, with mass yield of concentrate and Fe grade selected as the main responses to the changing of the parameters. The results obtained were validated using the analysis of variance (ANOY A) and the mathematical model, which showed the variables as being significant to the investigation process, thus rejecting the null hypothesis. The significance of the variables was in the order of magnetic field intensity followed by pulsation frequency and lastly the percentage pulp solids. The model predictions and actual data were in good agreement, reporting regression coefficients ranging between 0.83 and 0.94. It was shown that a single stage magnetic separation has the potential to produce a 55% Fe product.
Keywords: Ore-dressing